WiSE CRT Is Beneficial for Heart Failure Patients as a Rescue Therapy: Evidence From a Meta-Analysis - Cang, Jiehui; Liu, Yaowu; Zhu, Didi; Liu, Shangshang; Shen, Junxian; Miao, Hongyu; Zhou, Qianxing; Chen, Long (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Leadless endocardial left ventricular (LV) pacing resynchronization therapy is a novel solution for patients with heart failure (HF) who failed conventional cardiac resynchronization therapy (CRT). Methods: PubMed and the Cochrane Library were searched for relevant cohort studies. Clinical outcomes of interest such as ejection fraction (EF), QRS duration (QRSd), left ventricular end-systolic volume (LVESV) at baseline and follow-up were extracted and analyzed. Results: Five studies which were of good quality and involved 175 HF patients for WiSE CRT were included, and patients were followed up for 6 months. The implanted success rate which ranged from 76.5% to 100%. WiSE CRT resulted in significantly narrower QRSd [mean difference (MD): -38.21ms, 95% confidence interval (CI): -44.36 to -32.07, P<0.001], improved left ventricular ejection fraction (MD: 6.07%, 95% CI: 4.43 to 7.71, I2 = 0%, P<0.001), reduced left ventricular end-systolic volume (MD=-23.47ml, 95% CI: -37.18 to -9.13, P<0.001), and reduced left ventricular end-diastolic volume (MD= -24.02ml, 95% CI: -37.01 to -11.03, P = 0.02). Conclusions: Evidence from current studies suggests that leadless endocardial LV pacing resynchronization is effective for HF patients who failed conventional CRT or needed an upgrade and it may be an interesting rescue therapy.